Malaria: transmission, diagnosis and treatment: A Review - Ritu, Sanjida Sultana; Dihan, Alaya Ferdous (Brac University, 2022)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2021.